Functional safety a straightforward guide to applying IEC 61508 and related standards - Smith, David John, 1943-; Simpson, Kenneth G. L. (Oxford ; Burlington, MA : Elsevier Butterworth-Heinemann, 2004)
A practical guide to designing and assessing safety-critical systems to international standards.
Cover; Functional Safety: A Straightforward Guide to applying IEC 61508 and Related Standards; Contents; A Quick Overview; Acknowledgements; 1 The meaning and context of Safety-Integrity targets; 2 Meeting IEC 61508 Part 1; 3 Meeting IEC 61508 Part 2; 4 Meeting IEC 61508 Part 3; 5 Meeting IEC 61511; 6 Reliability modelling techniques; 7 Failure rate and mode data; 8 Some comments on Part 6 of IEC 61508; 9 Second tier and related guidance documents; 10 Demonstrating and certifying conformance; 11 Pressure control system (exercise); 12 Burner control assessment (example)
Includes bibliographical references (p. [252]-254) and index.
Keywords: Industrial safety -- Standards -- European Union countries; Process control -- Standards -- European Union countries; Manufacturing processes -- Safety measures -- Standards -- European Union countries; Electronic books